Moderate alcohol consumption is associated with lower chronic disease burden expressed in disability-adjusted life years: a prospective cohort study - Beulens, J.W.J.; Fransen, H.P.; Struijk, E.A.; Boer, J.M.A.; de Wit, G.A.; Onland-Moret, N.C.; Hoekstra, J.; Bueno-de-Mesquita, H.B.; Peeters, P.H.M.; May, A.M. (Kluwer (now part of Springer), 2017)
The relation of alcohol consumption with disease burden remains debated partly due to opposite associations with cardiovascular disease (CVD) and cancer. The relation of alcohol consumption with disease burden expressed in disability-adjusted life years (DALYs) summarizes opposing associations of alcohol consumption on chronic diseases. This study aimed to investigate the association of alcohol consumption with chronic disease burden expressed in DALYs based on individual-participant data. The study was a prospective study among 33,066 men and women from the EPIC-NL cohort. At baseline, alcohol consumption was assessed with a validated food-frequency questionnaire. Participants were followed for occurrence of and mortality from chronic diseases and DALYs were calculated. After 12.4 years follow-up, 6647 disease incidences and 1482 deaths were documented, resulting in 68,225 healthy years of life lost (6225 DALYs). Moderate drinkers (women 5–14.9 g/day, men 5–29.9 g/day) had a lower chronic disease burden (mean DALYs −0.27; 95% CI −0.43; −0.11) than light drinkers (0–4.9 g/day), driven by a lower disease burden due to CVD (−0.18: −0.29; −0.06) but not cancer (−0.05: −0.16; 0.06). The associations were most pronounced among older participants (≥50 years; −0.32; −0.53; −0.10) and not observed among younger women (−0.08; −0.43; 0.35), albeit non-significant (pinteraction > 0.14). Substantial drinking (women 15–29.9 g/day, men 30–59.9 g/day) compared to light drinking was not associated with chronic disease burden. Our results show that moderate compared to light alcohol consumption was associated with living approximately 3 months longer in good health. These results were mainly observed among older participants and not seen among younger women.